From the Cancer Stage of Capitalism to the Political Principle of the Common: The Social Immune Response of "Food as Commons" - Nick Rose (Kerman University of Medical Sciences, 2021)
Background Critical scholars agree that contemporary globalised and industrialised food systems are in profound and deepening crises; and that these systems are generative of accelerating multiple crises in the earth's life systems. Why and how did we arrive at this point? This paper argues that, conceiving each individual human as one cell in the greater human body, we are afflicted by what John McMurtry termed 'the cancer stage of capitalism.' This provocative framing is adopted here in response to growing calls by climate, earth and physical scientists not to 'mince words' in the description and analysis of humanity's current predicament, but rather 'tell it like it is.'   Methods  Proceeding from McMurtry's application of the seven defining medical properties of a 'cancer invasion [of] an individual organism' to the broader body politic and the earth's life system, this paper draws on literature from diverse disciplines to investigate the fundamental cause of food systems crises. The paper references several empirical studies and meta-reviews that indicate the hastening decline in the integrity of human and ecological health, with a particular focus on the grain-oilseed-livestock complex and the accompanying social and ecological impacts on the southern cone countries of South America.   Results  The cause of food system crises is to be found in the core logic of capital accumulation, the profit imperative, and the relentless and expanding processes of commodification and financialization. The key metric of 'economic growth' is problematised and discussed. An embryonic 'social immune response' is now observable, in the diverse practices of decommodification, proposals for de-growth and commoning that together constitute an emerging 'food as a commons' movement.  ConclusionAs currently framed, the Food as Commons proposal lacks coherence, rigour and a viable strategy to move beyond the current crisis. Its transformative potential can be strengthened through a more explicitly political grounding based on appeals to and support of anti- and post-capitalist movements and initiatives.